Compliance of the plots elongation parameter in the study of the spatial structure of land - Gniadek, Jacek; Szewczyk, Robert (International Conference “Environmental Engineering”, 2017)
The study will present the results of research, including comparative analysis of the parameters of spatial shaping of plots, obtained by two independent methods for the same area: The first method – commonly used in studies of the spatial structure, requiring the use of several information tools and the second one – simpler with different methodological approach. The starting material will be the data included in the descriptive part of the real estate cadastre and on the digital map of the land and buildings registry. The basic element of the research will be continuous parts of parcels covered by one form of use. Detailed analysis will concern determination of the scale of differences for the studied parameters in both methodological variants. As a consequence this will determine the possibility of interchange ability of both methods in the works related to the assessment of rural land systems.